Reactive power optimization using successive quadratic programming method - Grudinin, N. (IEEE transactions on power systems, 1998)
This paper presents a reactive power optimization model that is based on successive quadratic programming (SQP) methods. Mathematical formulation and unified algorithm suppose different objective functions (OF) of reactive power optimization, depending on type and purposes of current reactive power control or planning problem. A bicriterion reactive power optimization model, that represents compromise between economical and security objective functions, is proposed. An efficient algorithm for approximation of initial problem by quadratic programming problem is described. The quadratic programming problem (QP) is solved on the basis of the Newton type quadratic programming method. A modified successive quadratic programming method was developed, that provides reliable convergence of the SQP method.